Masks in Medieval Armenian Sculpture - Hakobyan, Zaruhi A. (Actual Problems of Theory and History of Art, 2015)
Among zoomorphic and anthropomorphic images in medieval sculpture of Armenia the most mysterious and, one would say, not traditional enough are the so-called masks. The motif of mask has not yet been the subject of precise study in the context of Armenian art. Furthermore, there are no interpretations on this motif in the Eastern Christian studies, although the images of masks are known in Byzantine and Old Russian art. So the study we have focused on is very topical. In Medieval Armenian sculpture masks would appear in the décor of the churches of different historical periods: in 5th–6th, 7th and 10th–11th centuries, and we see them at such churches as St. Cross on Aghtamar, Saint Peter and Paul in Tatev, Sisavan, Bajburd, and so on. Notably, these certain motifs appear in the décor of high-ranking churches. As a rule, masks on the Armenian monuments are anthropomorphic (male and female images), and it should be noted that they are located in the significant space zones from the sacral point of view, i.e. on the eastern façade, on cornice or the tympanum. It is known that masks are widespread in both Eastern and Western Christian art. Based on the reference to the antique heritage, popularity of the motif in certain historical periods is evident. The mask motif entered Medieval Armenian art via East-Christian tradition maintaining its iconographic and symbolic characteristics.
Keywords: mask; image; human heads; sculpture; outer decoration; Aghtamar; Tatev; Bajburd; Sisavan